Environmental DNA Sampling of Small‐Bodied Minnows: Performance Relative to Location, Species, and Traditional Sampling. (24th September 2019) - Robinson, Anthony T.; Paroz, Yvette M.; Clement, Matthew J.; Franklin, Thomas W.; Dysthe, Joseph C.; Young, Michael K.; McKelvey, Kevin S.; Carim, Kellie J.
Abstract: We performed experiments in southwestern USA streams to evaluate the efficacy of environmental DNA (eDNA) sampling for two rare small‐bodied minnows: Spikedace Meda fulgida and Loach Minnow Rhinichthys cobitis . We collected eDNA by filtering 5‐L samples and compared detection sensitivity of eDNA assays to traditional sampling methods (electrofishing and seining) by using both techniques at 33 sites in seven streams. We used caged‐fish experiments to estimate eDNA production rates, persistence, and travel distances and to estimate relationships between fish density, biomass, and eDNA quantity. Loach Minnows were detected at 22 sites by both eDNA and traditional sampling, were not detected by either technique at 7 sites, and were detected only by eDNA at 4 sites. Spikedace were detected with both techniques at 15 sites, were not detected by either technique at 8 sites, and were detected only by eDNA at 7 sites. In the Verde River and Wet Beaver Creek, both species' eDNA was detected downstream of caged fish out to our maximum sampling distance of 500 m. Estimated eDNA production rates were greater for Spikedace than for Loach Minnows, although more Spikedace were used. Production rates for both species were greater in the Verde River than in Wet Beaver Creek. Persistence of eDNA did not differ among species but was greater in Wet Beaver Creek than in the Verde River. In density experiments, the amount of Spikedace eDNA was positively related to the density and biomass of caged Spikedace, but the relationship differed between streams. We conclude that eDNA surveys are more sensitive than traditional methods for detecting rare minnows in southwestern streams. With the sensitivity to detect even a single fish in a 100‐m reach, managers will be able to more effectively identify reaches occupied by threatened or endangered fish, even if a population is in decline.